La afectividad y la comunicación de los padres en el desarrollo emocional de los niños y niñas de cuatro a doce años de la escuela Omar Torrijos de San Isidro, Tenta, Saraguro, provincia de Loja, periodo lectivo 2012-2013 - Torres Mora, Dolores Elvira (2014)
This research study sought to ascertain affectivity and parent communication in the emotional development of children from 4-12 years of school Omar Torrijos of San Isidro, Tenta, Saraguro, Loja during the period 2012-2013 . He was raised as a general objective: to determine the incidence of emotional deprivation and parental communication on the emotional development of children from 4-12 years of school Omar Torrijos.Las specific hypotheses that guided the research are: to emotional deprivation of parents and their disclosure and its impact on their emotional development. The methods used were: deductive, inductive, descriptive and statistical. The techniques applied were interviewed teachers, parent survey and direct child observation. The total population was 4 teachers, 19 parents and 50 children / as. The main results that have arrived are: poor communication to parents maintain a negative impact on the emotional development of children. Another result is that parents pay little attention to the emotional needs of their children, because that is authoritarian, generating emotional imbalance, creating low self-esteem in children and lack of interest in school activities.